2021
DOI: 10.3390/ijerph182312504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seven-Year Fertilization Reclamation on Bacterial Community in a Coal Mining Subsidence Area in Shanxi, China

Abstract: The restoration of soil fertility and microbial communities is the key to the soil reclamation and ecological reconstruction in coal mine subsidence areas. However, the response of soil bacterial communities to reclamation is still not well understood. Here, we studied the bacterial communities in fertilizer-reclaimed soil (CK, without fertilizer; CF, chemical fertilizer; M, manure) in the Lu’an reclamation mining region and compared them with those in adjacent subsidence soil (SU) and farmland soil (FA). We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…VPA and correlation analysis further showed that SOM had a positive effect on soil microbial diversity ( Figure 7 ). Studies have shown that the increase of SOM can promote soil agglomeration, improve soil physical properties and nutrients, thereby promoting the growth and recovery of bacteria in reclaimed soil ( Li L. et al, 2021 ). Meanwhile, SOM plays a key role in plant growth and directly affects soil bacterial diversity ( Zeng et al, 2016 ; Li W. et al, 2021 ; Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…VPA and correlation analysis further showed that SOM had a positive effect on soil microbial diversity ( Figure 7 ). Studies have shown that the increase of SOM can promote soil agglomeration, improve soil physical properties and nutrients, thereby promoting the growth and recovery of bacteria in reclaimed soil ( Li L. et al, 2021 ). Meanwhile, SOM plays a key role in plant growth and directly affects soil bacterial diversity ( Zeng et al, 2016 ; Li W. et al, 2021 ; Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These fungal isolates exhibited the great ability to solubilize P, increase the growth of eggplant, and produce siderophores and indole acetic acid [6]. In addition, the use of organic residues as amendments exerts a great influence on soil microbial communities [45][46][47][48], which not only increases the soil organic matter level and long-term soil fertility, but also improves the soil health and productivity.…”
Section: Effects Of Different Organic/chemical Amendments In Rhizosph...mentioning
confidence: 99%
“…Previous research reports on land reclamation mainly focus on coastal reclamation, such as the USA 6 , the Netherlands 7 , Japan 8 (Suzuki.,2003), China 9 11 and Mexico 12 , which have carried out coastal reclamation for agriculture, mariculture, industrial use, urban development, and recreation. In addition, reclamation of mining areas is also a research hotspot, such as Li et al 13 and Gao et al 14 studied the methods and effects of reclamation in mining areas. However, there are few research reports on the reclamation of abandoned homesteads at home and abroad.…”
Section: Introductionmentioning
confidence: 99%